Editorial - Gráinne Conole (Association for Learning Technology, 2000)
At times of major educational change we are reminded of those things of lasting value which are of formative significance for learning and teaching - those things which empower students to gain riches in the form of knowledge, understanding and skill. At the threshold of the twenty-first century it is good to acknowledge, again, that our main job as educators, learning technologists and researchers is at all times to encourage and foster such richness in all of our students. Learning technology has an exceptionally productive potential role to play in this empowerment: the role of the Association of Learning Technology in promoting good practice in the use of learning technologies is therefore particularly highlighted at the start of a new century.